2018
DOI: 10.1002/alr.22142
|View full text |Cite
|
Sign up to set email alerts
|

Solitary chemosensory cells producing interleukin‐25 and group‐2 innate lymphoid cells are enriched in chronic rhinosinusitis with nasal polyps

Abstract: These data support SCC and ILC2 expansion as well as increased IL-25 production in nasal polyps and may represent early events in the pathogenesis of CRSwNP. IL-13 stimulates proliferation of SCC in a feed-forward loop, a process that is steroid-sensitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 53 publications
(61 reference statements)
3
55
0
Order By: Relevance
“…65 Recently, Kohanski et al demonstrated that SCCs are the primary epithelial source of IL-25 in the sinonasal epithelium. 19 Furthermore, similar to murine models, data support that humans have a similar feed-forward loop in which IL-25 from SCCs activate downstream IL-13, that then drives SCC expansion and further enhances IL-25 production 23 (Figure 1). …”
Section: Novel Cell Types Involved In Epithelial-mediated Type-2 Inflmentioning
confidence: 59%
See 3 more Smart Citations
“…65 Recently, Kohanski et al demonstrated that SCCs are the primary epithelial source of IL-25 in the sinonasal epithelium. 19 Furthermore, similar to murine models, data support that humans have a similar feed-forward loop in which IL-25 from SCCs activate downstream IL-13, that then drives SCC expansion and further enhances IL-25 production 23 (Figure 1). …”
Section: Novel Cell Types Involved In Epithelial-mediated Type-2 Inflmentioning
confidence: 59%
“…22 In humans, high IL-25 was found to be correlated with higher ILC2s. 23 Moreover, IL-13 produced by activated ILC2s has been found to be acting in a feed-forward loop to further propagate IL-25 production. 19,23 …”
Section: Cellular Sources and Function Of Tslp Il-25 And Il-33mentioning
confidence: 99%
See 2 more Smart Citations
“…Longer‐term studies, and studies of other antibiotics are clearly warranted given what we now know with regard to the importance of the sinonasal microbiome to sinus health. In a further study of the T helper 2 (Th‐2) response in nasal polyposis, Patel et al . further evaluate the role of solitary chemosensory cells (SCCs) in the production of interleukin‐25 (IL‐25) in nasal polyp tissue and provide further support for a proposed model in which IL‐25 produced by SCCs stimulates the group 2 innate lymphoid cells; this then results in the release of IL‐4, IL‐5, and IL‐13.…”
mentioning
confidence: 99%